Poligami Dalam Perspektif Hukum: Studi Perbandingan Hukum Islam Dan Hukum Positif di Indonesia - Indra Pratama; Sukiati; Iwan (Journal of Islamic Education and Law, 2026)
This paper aims to examine the psychological dilemma of conflicting feelings, thoughts, or emotions toward an object, person, or situation. This study examines the regulation of polygamy through a comparative study of Islamic law, Indonesian positive law, and the legal frameworks of Western European countries. Polygamy remains a crucial issue, intersecting the domains of theology, human rights, and public policy. The fundamental difference between these three systems lies in their philosophical emphasis: Islamic law focuses on moral justice, Indonesian law on administrative legality, and Western Europe on secularism and universal gender equality. This study concludes that, despite these stark differences, global legal trends are shifting toward protecting the domestic rights of women and children, regardless of the legal status of polygamy itself.